Peran Pancasila dalam Membentuk Karakter Kewarganegaraan bagi Mahasiswa - Chika Sindia Aprilia; Erik Khairudin Saputra; Hetika Sari (IJOCE: Indonesia Journal of Civic Education, 2022)
This study aims to describe the role of Pancasila in the effort to form student citizenship characters through a value-based approach to learning Pancasila courses in universities so as to create good citizens. The method used in this research is descriptive qualitative literature study, using data sources of journal literature, books and relevant scientific research. The results of the study show that Pancasila as a medium of character education is not just introducing values ​​to students, but also must be able to internalize values ​​based on Pancasila so that it functions as a charge of conscience so that it is able to awaken its appreciation and practice as citizens, these values ​​will compose mental and moral resilience when there is a meeting between conflicting values. The conclusion of the study is that the existence of Pancasila in the student learning process in higher education is closely related to the formation of the character of civic values ​​in order to achieve the attributes of civil society which are characterized of Pancasila. Keywords: Citizenship Character, Values, Pancasila.